Orientalism : history, theory, and the arts - Mackenzie, John (Viva books, 2012)
This study provides the first major discussion of Orientalism by a historian of imperialism. setting the analysis within the context of conflicting scholarly interpretation. author then carries the discussion into wholly new areas, testing the notion that the western arts received genuine inspiration from the east by examining the visual arts, architecture, design, music and theatre